2015
DOI: 10.1039/c5ra20870j
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of metal-doped calcium oxalate

Abstract: Calcium oxalate crystals are the most common biominerals found in plants. They also make their presence known as painful kidney stones in humans and animals. Their function in plants is extraordinarily versatile and encompasses calcium storage and defense mechanisms against herbivores and detoxification processes. Since plants containing calcium oxalate crystals are often exposed to metallic environments, we studied the interaction of such environmental metals with calcium oxalate in vitro. We showed that sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 31 publications
2
14
0
Order By: Relevance
“…The measurements of Cd removal are consistent with a process of constant partitioning of Cd into solid solutions possessing the Ca-Ox structure, in agreement with previous data by Weber et al [11]. A separate experiment in which Ca was not added to solutions containing Cd and oxalate showed that no Cd was precipitated from solutions unless the dissolved Cd concentrations exceeded about 1.3 x 10 -4 M (Fig.…”
Section: And Zn Partitioning From Solution Into Ca-oxalate Precipitatessupporting
confidence: 91%
See 3 more Smart Citations
“…The measurements of Cd removal are consistent with a process of constant partitioning of Cd into solid solutions possessing the Ca-Ox structure, in agreement with previous data by Weber et al [11]. A separate experiment in which Ca was not added to solutions containing Cd and oxalate showed that no Cd was precipitated from solutions unless the dissolved Cd concentrations exceeded about 1.3 x 10 -4 M (Fig.…”
Section: And Zn Partitioning From Solution Into Ca-oxalate Precipitatessupporting
confidence: 91%
“…Appreciable precipitation of Zn oxalate was measured at Zn mole fractions greater than 0.25 (Fig 1C). In agreement with these data, Weber et al [11] reported that Zn is not as readily incorporated into the crystalline Ca-Ox structure as Cd. Up to Zn mole fractions of 0.25, our data were consistent with a tendency for Zn to be largely excluded from the precipitated oxalate (Fig.…”
Section: And Zn Partitioning From Solution Into Ca-oxalate Precipitatesmentioning
confidence: 53%
See 2 more Smart Citations
“…All the O and N atoms of PASP-Im have a high degree of a negative charge, which means that PASP-Im can provide Ca 2+ with a large amount of binding sites. [35][36][37][38][39] As a result, the N and O atoms in the molecular structure of PASP-Im can be well bound to Ca 2+ ion, thereby inhibiting the growth of calcium carbonate crystals as well as the formation of calcium carbonate scales.…”
Section: Scale Inhibition Mechanism Of Pasp-im For Calcium Carbonatementioning
confidence: 99%